Research on Strategies and Technologies for Resource Management and Control of Heterogeneous Network of High and Low Orbit Satellites - Meirong ZHANG; Mengting HAO; Chuang WANG; Gengxin ZHANG (天地一体化信息网络)
With the vigorous development of space communication technology and the continuous advancement of space-integrated-ground information network, satellite communication networks resource management and control is becoming more and more complex.Due to the scarcity of satellite resources, the slowness of resource scheduling compared to the status refreshing, and uneven distribution of business, eff ciently managing resources has become one of urgent problems to be solved in the development of satellite communications.In view of the heterogeneous network system architecture of high and low orbit satellites, the challenges, its network resource management and control facing, were analyzed.Integrating on the basis of traditional management and control architecture, the collaborative management and control architecture based on group management was introduced.The management strategy of satellite network virtual resource pool was explained to relieved resources scarcity.Resource scheduling algorithms based on deep reinforcement learning(DRL) was introduced to solved the mismatch problem of traditional scheduling methods in complex environments.Beam-hopping technology was adopted to deal with the two-dimensional unevenness of service distribution in time and space.